التحليل اللاخطي الهندسي للبلاطات الرقيقة باستخدام طريقة العناصر المنتهية المعدلة - أبو دياب, سليمان; حسن, ابراهيم (Latakia University Journal -Engineering Sciences Series, 2018)
In this study, thin plates are analyzed using modified finite element displacement approach in the geometrical nonlinear case (large deflections , small rotations), wherein the displacement function of the rectangular plate element (ACM) which has 12 degrees of freedom, is modified by adding new terms to it in order to consider the effect of the external loading acting at the finite element level. As a result, we obtain shape functions consist of two parts a homogenous part related to the degrees of freedom of the element and a particular part (non homogenous) dependent on the element loading at the finite element level. An incremental iterative approach is used and stiffness matrixes, external force vector and new terms resulting from the application of the modified finite element approach is concluded by using the virtual displacement concept. A Matlab language code is developed for the analysis of thin plates, some examples are computed and plotted and the results of the displacements, stresses, strains and internal forces are compared with those produced by MSC Patran as well as the analytical solution. The comparison showed that the developed modified approach gave a solution closer to the exact solution than that of MSC Patran. even by using a finite mesh. التحليل اللاخطي الهندسي للبلاطات الرقيقة باستخدام طريقة العناصر المنتهية المعدلة تم في هذه الدراسة نمذجة و تحليل البلاطات الرقيقة عبر اعتماد مقاربة معدلة لطريقة العناصر المنتهية – نموذج الانتقالات – و ذلك ضمن المجال اللاخطي الهندسي (انتقالات كبيرة , دورانات صغيرة). حيث تم تعديل تابع الانتقال في طريقة الانتقالات التقليدية لعنصر البلاطة المستطيل ذو 12 درجة حرية المعروف بـ (ACM) و إضافة حدود جديدة تأخذ تأثير الحمولة الخارجية المؤثرة على البلاطة بعين الاعتبار, و نتيجة لذلك أصبحت توابع الشكل مؤلفة من جزأين : جزء متجانس متعلق بدرجات الحرية للعنصر و جزء آخر غير متجانس مرتبط بالحمولات الخارجية المؤثرة على العنصر. تم اعتماد المنهج التزايدي التكراري في الحل و تطبيقه على مبدأ الانتقالات الوهمية و استنتاج مصفوفات الصلابة, شعاع القوى الخارجية و الحدود الإضافية الناتجة عن الطريقة المعدلة. بالإضافة إلى ذلك تم تطوير كود برمجي في البيئة البرمجية للبرنامج المعروف الماتلاب (MATLAB) لتحليل البلاطات الرقيقة, و حسبت و رسمت مخططات الانتقالات, الإجهادات, التشوهات و قوى المقطع و درست بعض الأمثلة و قورنت بالنتائج التي يعطيها برنامج MSC Patran و مع الحل الدقيق أيضاً. بينت النتائج أن الكود البرمجي المطور للطريقة المعدلة أعطى قيم أقرب للحل الدقيق من برنامج MSC Patran و ذلك على الرغم من استخدام شبكة خشنة عند تقسيم البلاطة (عدد عناصر صغير نسبياً).